Nilai Persediaan, Aset Tetap, Ukuran Perusahaan, Kualitas Audit, Dan Audit Tenure Terhadap Audit Report Lag - Sarah Nuriela Sabatini; Mekani Vestari (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2019)
The purpose of research is to obtain empirical evidence of the effect of inventory value, fixed assets, firm size, audit quality and audit tenure on audit report lag by using the financial reports statements of manufacturing companies listed on the Indonesia Stock Exchange. The examined factors of this research are from inventory value, fixed assets, firm size, audit quality, and audit tenure as the independent variable, while the audit report lag as the dependent variable. The sample consists of 324 companies listed on the Indonesia Stock Exchange (IDX) and submitted financial reports to OJK in the period 2015-2017. The data that was used in this research was secondary data and selected by using purposive sampling method. This study used multiple linear regression as the analysis method. The results of this study indicate that the variable fixed assets, and the size of the company have a significant effect to the audit report lag, while the variable value of inventory, audit quality and audit tenure did not have significant effect to the audit report lag